2019
DOI: 10.1097/md.0000000000017130
|View full text |Cite
|
Sign up to set email alerts
|

Increased perihematomal neuron autophagy and plasma thrombin–antithrombin levels in patients with intracerebral hemorrhage

Abstract: Animal studies have demonstrated that autophagy was involved in neuronal damage after intracerebral hemorrhage (ICH). Several studies showed thrombin–antithrombin (TAT) plasma levels were elevated in patients with ICH. In this study, we aimed to evaluate if autophagy occurred in patients with ICH; and the relationship between the severity of brain injury and plasma TAT levels.A novel tissue harvesting device was used during hematoma removal surgery to collect loose fragments of tissue surrounding the affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Autophagy is a tightly regulated process for the bulk removal of degraded cytoplasmic macromolecules and organelles in mammalian cells via lysosomes, thus maintaining cell homeostasis [29]. A previous study demonstrated that the higher the level of autophagic neurons in patients with ICH, the greater the severity of neuronal dysfunction [30]. In our study, elevated LC3-II and decreased p62 in the ICH rat brain indicated excessive autophagy ux induced by brain injury.…”
Section: Discussionsupporting
confidence: 56%
“…Autophagy is a tightly regulated process for the bulk removal of degraded cytoplasmic macromolecules and organelles in mammalian cells via lysosomes, thus maintaining cell homeostasis [29]. A previous study demonstrated that the higher the level of autophagic neurons in patients with ICH, the greater the severity of neuronal dysfunction [30]. In our study, elevated LC3-II and decreased p62 in the ICH rat brain indicated excessive autophagy ux induced by brain injury.…”
Section: Discussionsupporting
confidence: 56%
“…Stroke is a major cause of disability, and has been one of the most referenced causes of mortality worldwide. Ischemic stroke and hemorrhagic stroke accounted for approximately 80% and 20%, respectively, of stroke cases [ 1 ]. Thus, reducing brain injury and improving the prognosis of ischemic stroke is becoming an urgent neurology problem.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accumulating evidences have shown that iron released from the hematoma contributes to autophagy activation after ICH [14][15][16], but it is unknown that this process induces a beneficial or detrimental effect. Most studies support the notion that ICH-induced autophagy exacerbated histological and neurobehavioral consequences [13,15,17]. In contrast, Duan et al found that activated autophagy exhibited neuroprotective effects against secondary brain injury via inhibiting endoplasmic reticulum stress at the early stage post-ICH [18].…”
Section: Introductionmentioning
confidence: 77%